2016
DOI: 10.1186/s12870-016-0764-x
|View full text |Cite|
|
Sign up to set email alerts
|

Contrasting transcriptional responses of PYR1/PYL/RCAR ABA receptors to ABA or dehydration stress between maize seedling leaves and roots

Abstract: BackgroundThe different actions of abscisic acid (ABA) in the aboveground and belowground parts of plants suggest the existence of a distinct perception mechanism between these organs. Although characterization of the soluble ABA receptors PYR1/PYL/RCAR as well as core signaling components has greatly advanced our understanding of ABA perception, signal transduction, and responses, the environment-dependent organ-specific sensitivity of plants to ABA is less well understood.ResultsBy performing real-time quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 53 publications
4
71
0
Order By: Relevance
“…These processes involve the expression of stress-response genes, many of which are regulated by ABA (Fan et al, 2016). Therefore, ABA as an important messenger regulates the adaptive response of plants to abiotic stress (Sah et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These processes involve the expression of stress-response genes, many of which are regulated by ABA (Fan et al, 2016). Therefore, ABA as an important messenger regulates the adaptive response of plants to abiotic stress (Sah et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similar structures also exist in other plants. Furthermore, the expression patterns of PYL genes have been studied in tissues and in responding to exogenous ABA and diverse stresses in multiple plants (Saavedra et al, 2010;Boneh et al, 2012;Kim et al, 2012;Bai et al, 2013;González-Guzmán et al, 2014;Tian et al, 2015;Fan et al, 2016;Gordon et al, 2016;Yu et al, 2016;Chen et al, 2017;Zhang et al, 2017). These findings provide valuable information for researchers to further examine the functions of PYLs in ABA signaling in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it is of great importance to enhance stress tolerance of cotton plants. One of the key strategies may be achieved via genetically engineering of PYL genes (Kim et al, 2014;Lee et al, 2015;Yu et al, 2016;Zhao et al, 2016;Chen et al, 2017;Liang et al, 2017). It is therefore essential for us to elucidate the functions and regulatory mechanisms of Gossypium PYLs.…”
Section: Introductionmentioning
confidence: 99%
“…1 Our recent results demonstrated that PYR1/PYL/RCAR ABA receptor genes in maize exhibit distinct expression patterns in response to abiotic stresses (or ABA) between roots and leaves, with isoforms that are upregulated in roots being down-regulated in leaves, and vice versa. 33 Except with the different downstream transcript factors, this receptor family themselves displays a clear development-specific features in transcription. PYL5 is the most highly expressed receptor at seed maturation, suggesting that it may play a major role in ABA response at this stage.…”
Section: Spatio-temporal Specificities Of Pyr1/pyl/rcar Aba Receptorsmentioning
confidence: 99%